Np(V) solubility, speciation and solid phase formation in alkaline CaCl2 solutions. Part II: thermodynamics and implications for source term estimations of nuclear waste disposal - Fellhauer, David; Altmaier, Marcus; Gaona, Xavier; Lützenkirchen, Johannes; Fanghänel, Thomas (Radiochimica acta, 2016)
Abstract The results of comprehensive solubility experiments with Np(V) in dilute to concentrated - CaCl2 solutions which included the spectroscopic investigation of the predominant aqueous - Np(V) species and the thorough analysis of the solubility controlling Np(V) solid - phases [1](Fellhauer, D., Rothe, J., Altmaier, M., Neck, V., Runke, J., Wiss, T., - Fanghänel, Th., Np(V) solubility, speciation and solid phase formation in alkaline - CaCl2 solutions. Part I: Experimental solubility (Radiochim. Acta, DOI 10.1515/ract-2015-2489), in the - following referred to as “Part I”), showed that the concentration of Np(V) in these - systems is limited by equilibrium reactions between previously unknown (qua)ternary solid - compounds, CaNpO2(OH)2.6Cl0.4 · 2H2O(s) (I), - Ca0.5NpO2(OH)2 · 1.3H2O(s) (II) and Ca0.5NpO2(OH)2(s) (III), and ternary aqueous complexes of Np(V) with - the general formulae Cax[NpO2(OH)2]2x-1, Cay[NpO2(OH)5]2y-4 with y ≈ 2.4 ± 1.5 (EXAFS result) and innersphere Np(V) chloro complexes, - Caz[NpO2Cl]2z+ with z = 0 and 1 (EXAFS result). A systematic thermodynamic - evaluation of the experimental solubility data based on the specific ion interaction theory (SIT) - and the Pitzer approach is performed. The stoichiometries of the ternary hydrolysis complexes are - assessed as Ca[NpO2(OH)2]+ and Ca3[NpO2(OH)5]2+. The corresponding - thermodynamic solubility and complex formation constants at I = 0 as well as the ion interaction - parameters (SIT and Pitzer) were derived yielding a comprehensive geochemical model for the - Np(V) solubility behavior in pH neutral and alkaline CaCl2 solutions over a large - range of ionic strengths. This significantly improves source term estimations for scenarios with - calcium dominated aquatic systems. The principally different behavior of Np(V) in - NaCl and CaCl2 solutions is highlighted, and the impact of the new findings on - geochemical modelling of systems relevant for nuclear waste disposal is discussed.
Gesehen am 15.05.2020